Surface-enhanced Raman spectroscopy and microfluidic platforms: challenges, solutions and potential applications. Issue 7 (9th March 2017) - Jahn, I. J.; Žukovskaja, O.; Zheng, X.-S.; Weber, K.; Bocklitz, T. W.; Cialla-May, D.; Popp, J.
Abstract : The review provides an overview of the development in the field of surface-enhanced Raman spectroscopy combined with microfluidic platforms. Abstract : The exhaustive body of literature published in the last four years on the development and application of systems based on surface-enhanced Raman spectroscopy (SERS) combined with microfluidic devices demonstrates that this research field is a current hot topic. This synergy, also referred to as lab-on-a-chip SERS (LoC-SERS) or nano/micro-optofluidics SERS, has opened the door for new opportunities where both techniques can profit. On the one hand, SERS measurements are considerably improved because the processes previously performed on a large scale in the laboratory and prone to human error can now be carried out in nanoliter volumes in an automatic and reproducible manner; on the other hand, microfluidic platforms need detection methods able to sense in small volumes and therefore, SERS is ideal for this task. The present review not only aims to provide the reader an overview of the recent developments and advancements in this field, but it also addresses the key aspects of fundamental SERS theory that influence the interpretation of SERS spectra, as well as the challenges brought about by the experimental conditions and chemometric data analysis.